The individualized instruction application for personal-social skills of students with intellectual disabilities - Ishartiwi Ishartiwi; Rendy Roos Handoyo; Wening Prabawati; Adi Suseno (Jurnal Cakrawala Pendidikan, 2023)
Individualized learning is an ideal form of intervention for students with intellectual disabilities due to the ability to accommodate the learning requirements of personal-social skills. Although there are contradictions in its implementation, special education teachers have tried to implement it. This survey research aims to identify teachers' experiences in carrying out individualized learning including aspects of forms, constraints, and impacts on students' personal-social skills. The data collection was retrieved through a questionnaire instrument fulfilled by 116 special education teachers in Yogyakarta, who were determined by purposive sampling and analyzed descriptively and quantitatively. The result shows that 88,2 % of teachers apply individualized instruction methods in the form of a classical learning design with functional academic material content. The main obstacle comes from teachers' perception regarding students' condition heterogeneity, which resulted in difficulties in designing the learning activity. The impact on personal-social skills for all aspects shows that 50%-80% of students are able to improve their skills through practice and repetition. In conclusion, individualized instruction applications varied according to teachers' perceptions. While constrained to accommodate each student's requirement, this learning method resulted in a positive impact on skill learning outcomes.